EXAMINING METAPHORS AND THEIR SIGNIFICANCE IN LADY WHISTLEDOWN'S STATEMENTS IN THE BRIDGERTON SERIES - Aidil Syah Putra; Rizka Salsabiila Syahan; Sita Ardelia (VARIABLE RESEARCH JOURNAL, 2024)
Metaphor is a way for understanding the core function of one term via the lens of another when the two phrases share similarities or correlate. Nowadays, figurative language, including metaphor, is used in speech, narrative writing, and film dialogue. This is significant since the usage of metaphor has made the majority of the talks more clever. This research will look at Lady Whistledown's figurative expression in the Bridgerton film series and discuss its significance. This is a qualitative study, with data and conclusions presented rationally. The data for this study was examined utilizing Beekman and Callow's metaphor theory. The author identified two types of metaphors: full metaphors and abridged metaphors. The study's findings identified one Full Metaphor, seven Abbreviated Metaphor kinds 1, nine Abbreviated Metaphor types 2, twelve Abbreviated Metaphor types 3, and four Abbreviated Metaphor types. Each metaphor's meaning was defined by its environment.